Workplace violence and its associated factors among nurses working in university teaching hospitals in Southern Ethiopia: a mixed approach - Anose, Bereket Hegeno; Roba, Adem Esmael; Gemechu, Zegeye Regassa; Heliso, Asnakech Zekiwos; Negassa, Segni Begna; Ashamo, Teshale Belayneh (Frontiers in Environmental Health, 2024)
Background: Workplace violence among nurses has increased dramatically in the last decade.Still, mitigation techniques have not been well explored; many studies used a quantitative research approach, and there is a knowledge gap on the current status of workplace violence. The aim of this study was to assess the prevalence of workplace violence and associated factors among nurses working at university teaching hospitals in the South Region of Ethiopia.Methods: An institution-based cross-sectional study was conducted using a mixed approach. A random sample of 400 nurses was interviewed for the quantitative analysis, and nine key informants were interviewed for the qualitative analysis. Descriptive statistics were used to summarize the data. A logistic regression model was used to analyze the data. An adjusted odds ratio with a 95% confidence interval and a corresponding p-value < 0.05 was used to determine the association between variables. The qualitative data were transcribed and translated, then themes were created, followed by thematic analysis using Open Code version 4.02.The prevalence of workplace violence was 61.3% within the last 12 months. Nurses working in emergency departments [AOR = 4.27, 95% CI: 2.21, 8.24], nurses working in inpatient departments [AOR = 2.58, 95% CI: 1.40, 4.72], the number of nurses in the same working unit from one to five [AOR = 2.36, 95% CI: 1.21, 4.63], and six to ten staff nurses [AOR = 2.12, 95% CI: 1.17, 3.85], nurses routinely making direct physical contact [AOR = 2.77, 95% CI: 1.55, 4.95], and nurses' work time between 6 pm and 7 am [AOR = 1.68, 95% CI: 1.00, 2.82] were factors significantly associated with workplace violence.In this study, the prevalence of workplace violence against nurses was high. We identified factors significantly associated with workplace violence among nurses. Interventions should focus on early risk identification, the management of violent incidents, and the establishment of violence protection strategies that consider contextual factors to reduce workplace violence.